Examining the Relationship of Online Social Networking Sites’ Activities, Customers’ Brand Choice, and Brand Perception in Health-Related Businesses - Nazir, Mehrab; Tian, Jian; Hussain, Iftikhar; Arshad, Adeel; Shad, Muhammad Afzal (Frontiers in Psychology, 2020)
The purpose of current study is to examine the effect of online social networking sites activities on brand choice for health-related businesses and in addition to this study also explored the mediating impact of brand perception on the connection of online social networking sites activities and brand choice in health-related business. Data was collected through a self-administered questionnaire from 300 customers, randomly selected from health sector businesses in Lahore and Faisalabad. The study findings indicate that online social networking sites activities had a substantial influence on customers’ brand choice in health-related businesses and brand perception mediates the connection among online social networking sites activities and customers’ brand choice in health-related businesses. Findings of current research recognized the increasing significance of online social networking sites in health-related businesses. The study also offers visions for health-related companies and their managers on visualizing brand perception.